SAT0264 Impact of uveitis on the phenotype of patients with recent inflammatory back pain. Data from the desir cohort. (23rd January 2014) - Wendling, D.; Prati, C.; Demattei, C.; Miceli-Richard, C.; Daures, J.-P.; Dougados, M.
Abstract : Background: Influence of uveitis on clinical, epidemiological and imaging features in patients with inflammatory back pain (IBP) related to spondyloarthritis (SpA) needs to be known. Objectives: To determine the prevalence of uveitis in patients with recent IBP suggestive of SpA, and to investigate the influence of uveitis on the overall features of patients presenting with recent IBP. Methods: The DESIR cohort is a prospective, multicenter French cohort of patients with early IBP (Calin or Berlin criteria) (>3 months and <3 years of duration) suggestive of SpA according to the investigator, including 708 patients (mean age 33.8 years, 53.8% female, 57.3% HLA B27 positive). Uveitis was defined by an ophthalmological episode diagnosed as uveitis by an ophthalmologist, or a painful red eye episode of at least 48 hours duration and/or necessitating local steroids. Data on the baseline demographic characteristics, functional status and quality of life, imaging features (standard X-Rays, MRI, Ultrasounds), BMD, and blood tests were compared in patients with and without uveitis. Both the date of the first symptom of IBP and the symptoms of uveitis were recorded, as well as the date of the visit. Factors associated with the presence of uveitis were identified both by uni and multivariate analysis (logistic regression). Results: The prevalence of uveitis in the DESIR cohort was 8.47% [95%CI 6.58-10.83] (n=60/708 patients). Uveitis occurred after the first symptoms of IBP in 45%, before in 37%, and simultaneously (±1month) in 18% of the cases. Presence of uveitis was significantly associated in univariate analysis with pain in cervical spine, infection preceding (less than 3 months) inflammatory disease, previous diagnosis of inflammatory bowel disease, some dimensions of SF36 (mental and physical health, relation), presence of Achilles enthesitis, elevated leukocyte count, serum creatinin levels, radiological hip involvement, and chronic sacro iliac MRI lesions. Uveitis is not associated with fulfilment of diagnosis criteria, HLA-B27, BASDAI, BASFI, ASDAS, BMD. A stepwise multivariate analysis found an association between uveitis and: pain in cervical spine, infection preceding inflammatory disease, previous diagnosis of inflammatory bowel disease, physical health limitation of SF36 (Table). Conclusions: In recent IBP suggestive of SpA, uveitis is associated with some particular rheumatologic and extra rheumatologic features. Our data, and in particular the association with IBD and infection might suggest a role of environmental factors in the incidence of uveitis in SpA. Disclosure of Interest: None Declared